Comparison of Effectiveness between Combination of Beta-Lactam with Azyhtromycin or Levofloxacin for Adult Pneumonia Patients - Arifah, Gina; Halimah, Eli; Abdulah, Rizky (Pharmacology and Clinical Pharmacy Research)
Treatment for pneumonia has always been a challenge due to the difficulties in diagnosis and the growing incidence of antibiotic resistance. Beta-lactam antibiotics are the first line treatment for pneumonia. The combination of beta-lactam with other antibiotics are preferred than single antibiotic therapy. However, there was limited information regarding the effectiveness of combination between beta-lactam with either macrolides or fluoroquinolone for the treatment of pneumonia.The purpose of this study was to determine the most effective combination of antibiotics for hospitalized adults pneumonia patients. This was a cross-sectional study with prospective data collection. The data source was the medical record of the subjects. We included adult pneumonia patients hospitalized at Dr. Hasan Sadikin General Hospital during June-August 2015. We found that mean reduction of body temperature in group who received combination of a beta-lactam antibiotic and azithromycin was 1.53 0C, while in levofloxacin group, the reduction was 1.22 0C (p=0.210). Reduction in leukocytes and respiratory rate were 7800 and 2.29 times/minute, respectively, in the former group, while in the latter group the reduction of leukocytes and respiratory rate were 2600 and 5 times/minute. The differences were not statistically significant in both parameters (p=0.036 and 0.149, respectively). In conclusion, better clinical outcomes were observed in patients treated with combination of beta-lactam and azithromycin compared to combination of beta-lactam and levofloxacin, although the difference was not statistically significant.Keywords: pneumonia, pneumonia therapy, combination therapy for pneumonia